Une constellation nommée Argo – L’errance dans la science-fiction vidéoludique - Jean-Charles Ray; Simon Laperrière (ReS Futurae)
Be it in Mad Max (Miller, 1979), Ulysses 31 (Chalopin & Wolmark, 1981) or Farscape (O’Bannon, 1999), the wanderer is an important figure of science-fiction. Post-apocalyptic worlds, unknown constellations and parallel dimensions, as futuristic terrae incognitae, allow for never ending, wanderings stamped by randomness, danger and a loss of ////. It is no wonder that video games took over these worlds to turn them into exploration playgrounds. Let’s remember that, to Janet Murray, navigable space is one of the pillars of digital environments (Murray, 1997). From Star Trek (Gadlow, 1972) to No Man’s Sky (Hello Games, 2016), the model of the galaxy that Mathieu Triclot links to video games’ free roaming (Triclot, 2011) offers a truly fertile field of exploration. To enter Fallout (Black Isles, 1997), Dune (Cryo, 1992) or Captain Blood (Exxos, 1988), is to run the risk the anguish and fascination of losing oneself in strange places, sometimes wondrous sometimes frightening. The gamer’s wonderings reinstate the exploration specific to the genre : as one ventures among planets and spatial void, so does the other daydream of technological innovations. To study wandering thus allows to reflect on the intimate links between science-fiction and video games and the ever-furthering frontier of virtual and futuristic worlds.